1983
DOI: 10.1111/j.1464-410x.1983.tb06561.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenacetin‐Containing Analgesics and Cancer of the Bladder or Renal Pelvis in Women

Abstract: In a case-control investigation of 154 women with cancer of the bladder and 440 female population controls spanning the same age range, the relative risk for this cancer was 2.6 in consumers of phenacetin-containing analgesics and 2.7 in tobacco smokers. The relative risks for cancer of the renal pelvis, determined for 31 cases, were 5.4 with phenacetin and 4.7 with tobacco. Increasing consumption of either agent increased the risk for cancer at each of the two sites, while a synergistic rather than purely add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0
6

Year Published

1988
1988
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 10 publications
4
24
0
6
Order By: Relevance
“…Johansson and Wahlqvist (1977) reviewed a series of case reports which documented bladder cancer among individuals with a history of phenacetin abuse. These uncontrolled observations were later followed by a few case-control studies (Fokkens, 1979;McCredie et al, 1983;Piper et al, 1985;McCredie and Stewart, 1988). Although fairly strong associations between regular use and increased risk were found in these studies, a dose-response relationship was demonstrated only in the Australian study (McCredie et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johansson and Wahlqvist (1977) reviewed a series of case reports which documented bladder cancer among individuals with a history of phenacetin abuse. These uncontrolled observations were later followed by a few case-control studies (Fokkens, 1979;McCredie et al, 1983;Piper et al, 1985;McCredie and Stewart, 1988). Although fairly strong associations between regular use and increased risk were found in these studies, a dose-response relationship was demonstrated only in the Australian study (McCredie et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…These uncontrolled observations were later followed by a few case-control studies (Fokkens, 1979;McCredie et al, 1983;Piper et al, 1985;McCredie and Stewart, 1988). Although fairly strong associations between regular use and increased risk were found in these studies, a dose-response relationship was demonstrated only in the Australian study (McCredie et al, 1983). Experimental studies have found phenacetin to cause bladder cancer in rats (Johansson, 1981;Murai et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The association between acetaminophen, a major metabolite of phenacetin and bladder cancer risk has also been examined. In previous studies, phenacetin has been shown to be positively associated with risk of bladder cancer [36][37][38][39] and other transitional cell carcinomas in the renal pelvis and ureter. 37,38,[40][41][42][43] Additionally, animal studies have shown that acetaminophen can induce urinary bladder carcinomas in rats 44 and mice.…”
mentioning
confidence: 99%
“…In previous studies, phenacetin has been shown to be positively associated with risk of bladder cancer [36][37][38][39] and other transitional cell carcinomas in the renal pelvis and ureter. 37,38,[40][41][42][43] Additionally, animal studies have shown that acetaminophen can induce urinary bladder carcinomas in rats 44 and mice. 45 However, no associations have been reported between acetaminophen and bladder cancer risk in most, 21,39,46,47 but not all, 33 observational studies.…”
mentioning
confidence: 99%